P163 Improving a SLE-Quality indicator tool in an outpatient tertiary care setting. (23rd March 2020) - Chu, Jun; Poncio, Elaine; Ochoa, Isabel; Temesgen-Oyelakin, Yenealem; Davis, Michael; Gupta, Sarthak; Manna, Zerai; Chapman, Marquis; Chu, Eileen; Donnellan, Aidan; Hasni, Sarfaraz
Abstract : Background: The care for patients with lupus is complex as they may exhibit multiple concomitant medical and socioeconomic issues. To address all their needs according to the current guidelines is a daunting task in busy outpatient practices. However, incorporating quality indicators in patient care has been found to decrease mortality and morbidity, improve patient satisfaction, and reduce costs. To improve the quality of care following recommendations from published guidelines, ACR, and EULAR, we embarked on a comprehensive quality improvement project by developing a checklist tool that incorporates the major SLE-Quality indicators (SLE-QI). Method: The project was launched in October 2017. A SLE-QI checklist detailing quality indicators was created based on published recommendations for standard of care. The checklist included a set of 20 SLE-QIs that address several important aspects of SLE care including diagnosis and disease monitoring, general prevention strategies, screening for comorbidities, drug toxicity monitoring, assessment of renal disease, reproductive health, and quality of life in daily practice. A standardized document template for clinic visits was developed that incorporated these quality indicators. Clinic progress notes were reviewed weekly to determine if these indicators were used and addressed. If SLE-QIs were missing, efforts were made to reach out to providers to address the missing QIs. Results: At the beginning of the assessment, documentation of SLE-QIs was generally poor and inconsistent. For example, vaccinations was only at 60% compliance while screening for cardiovascular risk was only at 3% compliance. Since documentation was not standardized, it was difficult to assess if SLE-QIs were being done. Implementing SLE-QI in standardized notes resolved these concerns, bringing compliance close to 100% compliance for the 20 identified SLE quality indicators. Conclusion: Standardized progress notes incorporating QI indicators is a feasible strategy that helps streamline data extraction for future clinical research. Additionally, incorporating patient outcome tools improves the ability to perform treat-to-target strategies for SLE. This ongoing QI project may potentially improve overall patient outcomes and lead to reduce health care costs.